Collaboration among small and medium-sized enterprises as part of internationalization: A systematic review - Luciana Gondim de Almeida Guimar\~aes; Pierre Blanchet; Yan Cimon (Administrative Sciences, 2021)
This article performs a systematic review of the research literature on the forms of collaboration among small and medium-sized enterprises (SMEs) so that they reach the foreign market, since there is a lack of research focusing on the collaborative relationship between national companies as a strategic option for accessing the foreign market. In addition, we analyzed the articles to conceptually synthesized the elements that make up the business models of these collaborative forms of operating in the foreign market. Likewise, we analyzed real cases of collaborative processes among SMEs for the foreign market and highlight the contributions of governments in promoting actions to support these collaborations. We also show some directions for future research that were pointed out by the articles.
Keywords: 350; alliance; business model; cluster; collaboration; cooperation; export; governance; internationalization; network; small and medium enterprises